![image](https://tex.z-dn.net/?f=+%5Cleft+%5C%7B+%7B%7B+%5Csqrt%7Bx%7D%2B+%5Csqrt%7By%7D%3D8++%7D+%5Catop+%7B+x-y%3D16+%7D%7D+%5Cright.++%5C%5C+%5C%5C++x-y%3D%28+%5Csqrt%7Bx%7D%2B+%5Csqrt%7By%7D%29%28+%5Csqrt%7Bx%7D-+%5Csqrt%7By%7D%29%3D8%28+%5Csqrt%7Bx%7D-+%5Csqrt%7By%7D%29%3D16+%5C%5C+++%5Cleft+%5C%7B+%7B%7B%5Csqrt%7Bx%7D%2B+%5Csqrt%7By%7D%3D8%7D+%5Catop+%7B%5Csqrt%7Bx%7D-+%5Csqrt%7By%7D%3D2%7D%7D+%5Cright.++%5C%5C+2+%5Csqrt%7Bx%7D+%3D10+%3D%3E+%5Csqrt%7Bx%7D+%3D5%3D%3Ex%3D25++%5C%5C+25%3Dy%3D18+%3D%3E+y%3D9)
\sqrt{x} =5=>x=25 \\ 25=y=18 => y=9" alt=" \left \{ {{ \sqrt{x}+ \sqrt{y}=8 } \atop { x-y=16 }} \right. \\ \\ x-y=( \sqrt{x}+ \sqrt{y})( \sqrt{x}- \sqrt{y})=8( \sqrt{x}- \sqrt{y})=16 \\ \left \{ {{\sqrt{x}+ \sqrt{y}=8} \atop {\sqrt{x}- \sqrt{y}=2}} \right. \\ 2 \sqrt{x} =10 => \sqrt{x} =5=>x=25 \\ 25=y=18 => y=9" align="absmiddle" class="latex-formula">
Ответ: х=25
у=9